2022
DOI: 10.5946/ce.2022.035
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic diagnosis of gastric metastases from malignant melanoma: systematic review

Abstract: Background/Aims: Metastases of malignant melanoma (MM) are rare and associated with poor prognosis. The objective of this study was to analyze the clinical and endoscopic characteristics of MM gastric metastases by systematically reviewing cases and case series involving patients diagnosed using upper gastrointestinal endoscopy. Methods: The PubMed and LILACS databases were searched. Reports containing individual patient data were included. Outcomes such as clinical data, endoscopic findings, treatments, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…Patients who have only one distant metastatic site experience markedly better outcomes compared to those with two or more distant sites of metastasis [9]. Primary mucosal melanomas pose a higher risk of spreading to the stomach, with a prevalence rate of 6.2% [10].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who have only one distant metastatic site experience markedly better outcomes compared to those with two or more distant sites of metastasis [9]. Primary mucosal melanomas pose a higher risk of spreading to the stomach, with a prevalence rate of 6.2% [10].…”
Section: Discussionmentioning
confidence: 99%
“…En estómago suelen presentarse con náuseas, vómitos, sangrado y pérdida de peso; en la TC puede observarse nódulos murales o masas con o sin cavitación 1 . En endoscopia suelen encontrarse mayormente en curvatura mayor, cuerpo y fondo; puede presentarse como lesiones hiperpigmentadas con ulceración en su centro, tumores submucosos, elevados y ulcerados, o como masas con necrosis y melanosis 5 . En intestino delgado se presenta en el 51-71%, suele afectar principalmente yeyuno e íleon terminal; se presenta con dolor abdominal vago, pérdida de peso, anemia por deficiencia de hierro, cambio de patrón evacuatorio y sangrado.…”
Section: Comentariosunclassified
“…metastases often delay the diagnosis due to the lack of specific symptoms and signs, and most MM transferred to the stomach is detected at autopsy (5). Reggiani et al (2) found that 56% of MM had gastrointestinal metastasis, so gastrointestinal metastasis of MM needs great attention. We present this 60-yearold woman with MM to remind us that we need to pay attention to MM with gastric metastasis in clinical work and reduce unnecessary medical disputes.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant melanoma (MM) is a common malignant tumor in the limbs, which is highly invasive, often occurs as metastatic cancer, and has a very poor prognosis ( 1 ). A study shows that the overall survival rate at 2 years was only 4% ( 2 ). The common metastatic sites of MM are the inguinal, lungs, liver, and brain, which can also metastasize to the gastrointestinal tract ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation